The Effect of Red Ginger Warm Water Foot Soak Therapy on Pain Levels in Patients with Uric Acid in Curahtakir Village Tempurejo District Jember Regency - Ali Hasan, Nizar; Sasmiyanto; Widada, Wahyudi (Universitas Bondowoso, 2024)
ABSTRACT Backgroud: Gout pain is concentrated in the bones, joints, muscles, and tissues around the joints, especially in the joints of the toes, fingers, heels, knees, elbows, and wrists. Method: This study used Pre-experimental with Pretest-Posttest Group design. Result: The results of the study on the measurement of pain levels before the intervention obtained an average value of the pain level scale of 6.75 and after the intervention obtained an average value of the pain level scale of 5.27. Conclusion: The conclusion of this study is that there is a significant effect on pain levels in gout sufferers before and after being given red ginger warm water footbath therapy. Researchers' recommendations for future researchers, because this study still has limitations where using pre-experiments has weaknesses that cannot control other variables outside the research variables so that future researchers can use a higher research design.